An Evaluation of the Activity of Prepared Zinc Nanoparticles with Extracted Alfalfa Plant in the Treatment of Heavy Metals - Zainab Ridha Al-Bahadili; Abbas Ali Salih AL-Hamdani; Farqad Abdullah Rashid; Labeeb Ahmed Al-Zubaidi; Suha Mohamed Ibrahim (مجلة بغداد للعلوم)
The alfalfa plant, after harvesting, was washed, dried, and grinded to get fine powder used in water treatment. We used the alfalfa plant with ethanol to make the alcoholic extract characterized by using (GC-Mass, FTIR, and UV) spectroscopy to determine active compounds. Alcoholic extract was used to prepare zinc nanoparticles. We characterized Zinc nanoparticles using (FTIR, UV, SEM, EDX Zeta potential, XRD, AFM). Zinc nanoparticle with Alfalfa extract and alfalfa powder were used in the treatment of water polluted with inorganic elements such as Cr, Mn, Fe, Cu, Cd, Ag by (Batch processing). The batch process with using alfalfa powder gets treated with Pb (51.45%), which is the highest percentage of treatment. Mn (13.18%), which is the lowest percentage of treatment. The batch process with using Zinc nanoparticles gets the result treated with Pb(98.822%), which is the highest percentage of treatment, and Mn (10.31%), which is the lowest percentage of treatment. When comparing alfalfa powder and zinc nanoparticle, it has been found that the treatment with zinc nanoparticle is more efficient in the removal of inorganic pollutants.